Determinants in the Uptake of the Human Papillomavirus Vaccine: A Systematic Review Based on European Studies - Fernández de Casadevante, Victoria; Gil Cuesta, Julita; Cantarero-Arévalo, Lourdes (Frontiers in Oncology, 2015)
Background Cervical cancer is the fourth most common cancer affecting women worldwide. Since 2006, two Human Papillomavirus vaccines (HPVV ) have been licensed to protect women against the virus that causes cervical cancer. However, worldwide coverage remains unequal. Studies from the USA found strong evidence for differences in HPVV uptake by ethnicity and healthcare coverage. As the profile of ethnic groups and the healthcare system in the USA differ from countries in Europe where HPVV is free in most of the countries, we conducted a systematic review in order to analyze the determinants of HPVV uptake in Europe. Methods We performed a systematic Pubmed, Scopus and Science Direct search to find articles published from HPVV availability in European countries until April 2014. No age restriction was applied. We included all studies assessing factors associated with HPVV uptake. Uptake refers to either initiation and/or completion of the three dose vaccination program. Results Out of the 23 eligible studies, 14 were retrospective reviews of data, six were cross-sectional surveys and three were prospective cohort studies. Higher HPVV uptake was associated with ethnic majority populations, higher socio-economic status, regular cervical screening participation by the mother and having received previous childhood vaccinations. Conclusions Since the vaccine is offered for free in most of the European countries, the findings suggest that ethno-cultural and educational factors play an important role when it comes to HPVV uptake. Girls who were undervaccinated had also a lower uptake of standard childhood vaccines and mothers who were less likely to attend cervical cancer screening. This may indicate, that only few parents have specific concerns with HPVV, and that preventive health care should seek ways to target these vulnerable groups.